Distribution and abundance patterns of two parapagurid hermit crabs (Crustacea: Decapoda: Anomura) along the west and south coasts of South Africa. Issue 2 (2nd April 2020) - Wright, AG; Griffiths, CL; Fairweather, TP
Abstract : A series of over 6 000 research-trawl samples collected along the west and south coasts of South Africa between 1987 and 2014 were analysed for the presence and biomass of two parapagurid hermit crabs, Sympagurus dimorphus and Parapagurus bouvieri. The percentage of trawls that landed S. dimorphus and P. bouvieri and the mean caught biomass were higher on the west than on the south coast for both the more-abundant S. dimorphus (30.59 vs 5.81% success and 287.88 vs 31.37 kg km –2, respectively) and for the less-abundant P. bouvieri (13.76 vs 3.58% success and 38.56 vs 16.32 kg km –2, respectively). Very few parapagurids were caught shallower than 150 m; thereafter, the proportion of trawls containing hermit crabs increased, peaking over the depth range 201–250 m for S. dimorphus (54%) and 401–450 m for P. bouvieri (51%), and declining steadily thereafter. On the west coast, the relative caught biomass of S. dimorphus increased significantly from north to south, but there was no apparent latitudinal trend in relative biomass for P. bouvieri. Similarly, there was a significant decline in caught biomass of S. dimorphus with increasing longitude along the south coast, but no apparent trend for P. bouvieri. Although this represents by far the most comprehensive global analyses of distribution and abundance patterns for parapagurids to date, extremely little remains known about the biology and ecological relationships of these species, or indeed of other members of the group.